IMMUNOHISTOCHEMICAL EXPRESSION OF CXCR2 IN BREAST CARCINOMA AND ITS ASSOCIATION WITH ER, PR AND HER2/NEU STATUS: A CROSS-SECTIONAL STUDY FROM A TERTIARY CARE CENTRE (Asian Journal of Medical Research and Health Sciences, 2026)
Background: CXC chemokine receptor-2 (CXCR2) has emerged as a candidate cancer stem-cell related biomarker in breast carcinoma, with reported roles in epithelial–mesenchymal transition, angiogenesis, metastasis and chemoresistance. However, clinicopathological data on CXCR2 expression in routine breast carcinoma specimens remain limited. The present study evaluated CXCR2 immunohistochemical expression in breast carcinoma and assessed its association with estrogen receptor (ER), progesterone receptor (PR), HER2/neu status and clinicopathological parameters. Methods: This cross-sectional analytical study was carried out in the Department of Pathology, Era’s Lucknow Medical College and Hospital, Lucknow, India, over 20 months (April 2020 to November 2021). Fifty newly diagnosed, histopathologically confirmed cases of breast carcinoma were included. Formalin-fixed paraffin-embedded sections were stained with hematoxylin and eosin for diagnosis and grading. Immunohistochemistry was performed for ER, PR, HER2/neu and CXCR2. ER and PR were interpreted as positive or negative; HER2/neu was interpreted according to standard immunohistochemical criteria; CXCR2 immunoreactivity was categorized as low expression (score